Oral Hygiene Indirect Instruction and Periodic Reinforcements: Effects on Index Plaque in Schoolchildren - Rodrigues, Jonas Almeida; dos Santos, Patricia Aleixo [UNESP]; Baseggio, Wagner; Milori Corona, Silmara Aparecida; Palma-Dibb, Regina Guenka; Nordi Sasso Garcia, Patricia Petromilli [UNESP] (Journal Pedodontics Inc, 2009)
The aim of this study was to evaluate the effectiveness of the indirect instruction and the influence of the periodic reinforcement on the plaque index in schoolchildren. Forty schoolchildren aged from 7 to 9 years old were selected from a public school. After determining the initial O'Leary Plaque Index all schoolchildren were submitted to a program for oral hygiene through indirect instruction - "The Smiling Robot". The schoolchildren were divided into 2 groups: with and without motivation reinforcement. The index plaque exam was performed in both groups after 30, 60 and 90 days of the educational program. Comparing the groups, the plaque index decreasing could be observed in the group with reinforcement with statistically significant difference. For the group with reinforcement, statistically significant difference among the evaluations was found. For the group without reinforcement, significant decrease in the plaque index was found after 30 days when compared to the first, third and fourth evaluations. The indirect instruction with "The Smiling Robot "promoted a positive initial impact on the decrease of plaque index in the schoolchildren. The periodic reinforcements showed snore suitable results and significant reduction of the plaque index in the course of the evaluations.
Keywords: School based preventive programs; Motivation; Dental plaque; Oral hygiene